Jesús González Urueña and the teaching of dermatology at the Facultad de Altos Estudios of Mexico city, 1918-1923 (Tzintzun, Revista de Estudios Históricos, 2019)
In this paper the chair of dermatology at the Facultad de Altos Estudios from Mexico City, taught from 1918 to 1923 by the prominent doctor Jesús González Urueña, in order to train experts in this area of medicine is analyzed. Much of its activities focused on the study of tinea capitis, a disease of childhood, which at the time was a public health problem.